Forfatteroversigt. Navne og kontaktoplysninger om bidragydere - Lundgreen-Nielsen, Flemming; Bradley, S. A. J.; Pedersen, Kim Arne; Schjørring, Jens Holger (Grundtvig-Studier, 2004)
List of authors’ adresses